Errors in hypothesis as a methodological reflection subject of a teacher-researcher - A. F. Zakirova (Russian State Vocational Pedagogical University, 2021)
Introduction. The present article outlines the results of a theoretical and practical study of the mechanisms of hypothesis in scientific research on the problems of education.The current research is aimed to study the methodological resources for improving the quality of scientific research on the problems of education through understanding the errors in hypothesising as a methodological reflection subject of a teacher-researcher.Methodology and research methods are based on an activity-personal approach to the cognition of the education process and on research activities to investigate this process. In addition, the following areas of modern pedagogical science are used as the methodological framework of the study: the study of the axiological and conceptual foundations of scientific activity with an appeal to the cultural and historical concept; a hermeneutic phenomenological approach aimed at updating the interpretive potential of scientific texts; classical methods of theoretical analysis and synthesis, deduction and induction, comparison, modelling and extrapolation as tools for studying the research activities of a teacher, as well as methods of expert assessment and included observation. The methodology is based on the criticism of the methodological concept of inductivism and involves the addition of a hypothetical-deductive method with the idea of prolonged end-to-end hypothesising, based on reflexive reassessment and prevention of meaning-making errors by the researcher.Results. As a result of the study, the mechanisms of trans-level conceptualisation of pedagogical knowledge in the process of working out the methodological apparatus of scientific research were revealed. In addition to the existing ones, unconventional - special - requirements for scientific hypotheses are justified, aimed at updating their prognostic and diagnostic functions. The systematisation of hypothesis errors was carried out, which makes it possible to regulate reflexive scientific and pedagogical search, to carry out feedback in the process of methodological preparation and self-education, and to stimulate the development of scientifically justified heuristic pedagogical solutions. Methodological resources and positive results of using knowledge about the productive possibilities of preventive error management activities in the practice of training teachers-researchers are shown: pedagogical goals and installations of research activities, principles, specific didactic means of formation of methodological competence and error management.Scientific novelty. The phenomenon of hypothesis error was first described in the context of the conceptualisation and interconnection of elements of the methodological apparatus of scientific research, taking into account the prolongation, cumulativeness and trans-level of the hypothesis nomination process as a regulator of scientific search.Practical significance. The research results are recommended to be applied in the preparation of curricula for the course "Methodology of Scientific and Pedagogical Research" and as didactic material for academic studies in the process of teacher-researcher training in the framework of master's, postgraduate, doctoral and postgraduate self-education. The proposed typology of hypothesis errors is used in the development of methodological requirements for the scientific level of dissertation studies on the problems of education.